Course of neuropsychological health in post-COVID patients differs 6 and 12 months after inpatient rehabilitation - Müller, Katrin; Poppele, Iris; Ottiger, Marcel; Weber, Rainer-Christian; Stegbauer, Michael; Schlesinger, Torsten (Frontiers in Psychiatry, 2025)
BackgroundRehabilitation is an effective and feasible approach for post-COVID patients to improve mental health and cognitive complaints. However, knowledge regarding the long-term impact of rehabilitation on neuropsychological health of these patients is lacking.ObjectiveThis study aims to investigate psychological health, fatigue, and cognitive function 6 and 12 months after inpatient post-COVID rehabilitation of patients, who acquired COVID-19 in the workplace. In addition, group differences in these outcome parameters according to sex, age, acute COVID status, socioeconomic status, profession, and pre-existing diseases will be detected.MethodsThis longitudinal observational study examined the changes in mental and cognitive health of 127 patients with COVID-19 as an occupational disease or work accident. Symptoms of depression and anxiety, fatigue severity, somatic symptom severity, trauma-related symptoms, and cognitive functioning were assessed at the beginning as well as six and 12 months after rehabilitation. Group differences concerning sex, age, acute COVID status, socioeconomic status, occupational status, and existing diseases prior to COVID-19 were also analyzed.ResultsThe results showed that the improvements direct after rehabilitation in mental health and fatigue severity could not be maintained six and 12 months after rehabilitation discharge. Contrary, patients’ cognitive function maintained stable during follow-up. Significant group differences were observed regarding age, sex, acute COVID status, socioeconomic status, occupational status, and pre-existing diseases.ConclusionThis study highlights the importance of the aftercare process and the implementation of adequate and individualized therapeutic interventions such as psychological support and strengthen self-management skills.The study is registered in the German Clinical Trials Register with the identifier DRKS00022928.